2012
DOI: 10.23986/afsci.4999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two AM fungi on phytoplasma infection in the model plant Chrysanthemum carinatum

Abstract: Phytoplasmas are plant pathogenic bacteria, naturally transmitted by insects and confined in the phloem of the host plant, where they take up nutrients and eventually cause plant death. Their control is mainly based on insecticide treatments. The aim of this work was to study the effect of two AM fungi in modifying plant response to chrysanthemum yellows phytoplasma (CY) infection in chrysanthemum plants. Inoculation of Glomus intraradices BB-E and G. mosseae BEG12 reduced the damage caused by this plant patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…L. asiaticusinfected citrus were reduced after the application of Pi. In the case of phytoplasmas, although the correlation between Pi and the disease symptoms remains unclear, the disease symptoms in phytoplasma-infected plants could be reduced by the application of AM fungi (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012). AM fungi are symbiotic organisms that are able to enhance the uptake of Pi through up-regulation of Pi starvation responses in host plants (Branscheid et al, 2010;Gu et al, 2010;Volpe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. asiaticusinfected citrus were reduced after the application of Pi. In the case of phytoplasmas, although the correlation between Pi and the disease symptoms remains unclear, the disease symptoms in phytoplasma-infected plants could be reduced by the application of AM fungi (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012). AM fungi are symbiotic organisms that are able to enhance the uptake of Pi through up-regulation of Pi starvation responses in host plants (Branscheid et al, 2010;Gu et al, 2010;Volpe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Colonization by AM fungi can modify the plants' root architecture and enhance the uptake of mineral nutrients, in particular Pi (Gu et al, 2011;Volpe et al, 2013). Interestingly, several studies also reported that AM fungi reduce the disease symptoms caused by phytoplasmas (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012).…”
mentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) are symbiotic microscopic fungi belonging to the Glomeromycotina, subphylum of phylum Mucoromycota [ 20 ], able to positively influence plant performance in many ways, including by enhancement of heavy metal/metalloid stress tolerance [ 21 ]. AMF colonize the roots of most terrestrial plants [ 22 ], including ferns; once the symbiosis is established, they improve plant nutrition [ 23 ], modify root architecture [ 24 ], and promote plant tolerance or resistance to pathogens [ 25 , 26 , 27 ], drought [ 28 ], and salinity [ 29 ]. During phytoremediation, the use of AMF could positively affect the plant growth, mitigating the adverse effects of heavy metals and As or influencing their absorption, accumulation, and translocation [ 21 , 30 ].…”
Section: Introductionmentioning
confidence: 99%